Policy Analysis of Environmental Carrying Capacity to Improve Environmental Pilar Targets (SDGs) in Central Java - Irma Damayanti (Journal of Bioresources and Environmental Sciences, 2025)
The impact of global climate change has changed the cropping pattern system and the quality of carrying capacity and environmental capacity in accordance with current dynamics. Increased sea temperatures and the El-Nino and La-Nina phenomena cause changes in environmental conditions that affect monthly rainfall, thus disrupting the pattern and production of agricultural products. This study was conducted to ensure that the policy on carrying capacity and environmental capacity becomes a reference in all development planning documents in Central Java Province. The research objectives are analyzing the benefits and urgency of carrying capacity and environmental capacity in Central Java. And provide policy recommendations to integrate the carrying capacity and capacity of the environment in order to improve the achievement of the target indicators of sustainable development goals from the environmental sector as a basis for formulating sustainable development scenarios. The result of the study concluded that Central Java Province has not optimally implemented the carrying capacity and capacity policy in development planning so the negative impact of development in the form of environmental damage is still a priority issue in achieving sustainable development goals.